The Effect of Work Discipline and Communication on Employee Performance : Study at A Beauty Clinic in Bandung City - Qorry Febriyanti; Dedi Hadian; Senen Machmud (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
This study aims to determine the effect of work discipline and communication on employee performance at a clinic in the city of Bandung. The variables used are X1 = Work Discipline, X2 = Communication, and Y = Employee Performance. The questionnaire data is for employees at a beauty clinic in Bandung. To explain the relationship and influence between variables, researchers use descriptive verification research methods. In addition, this research also uses a case study approach with statistical testing using correlation, path analysis, and the coefficient of determination. The data analysis results show that the correlation coefficient test results have a value of 0.666, meaning that work discipline has a strong relationship with communication. Path analysis shows the Y = 0.577X1 + 0.347X2, where work discipline (X1) has an effect of 0.577 on employee performance and communication (X2) has an effect of 0.347 on employee performance. The coefficient of determination shows a result of 0.719 which means that work discipline and communication affect employee performance at a beauty clinic in the city of Bandung is 71.9%. In comparison, the remaining 28.1% is due to other factors.